Plastic Waste Habitats: Emerging Hotspots for Urban Mosquito Proliferation - Goud, Santhosh; Bhuyan, Kiran Bala; Banerjee, Ranjan; Patra, Sunita; Raj R, Vinay; Pradhan, Gyanendra (Journal of Neonatal Surgery, 2025)
Urbanization and the proliferation of plastic waste have converged to create novel ecological niches that facilitate the proliferation of container-breeding mosquitoes, including key disease vectors such as Aedes aegypti, Aedes albopictus, and Culex spp. This review explores the emergence of plastic waste habitats (PWHs) as critical hotspots for mosquito breeding in urban landscapes. While urban development has historically transformed natural habitats, the increasing accumulation of plastic debris provides abundant, long-lasting, water-holding microhabitats that support mosquito life cycles. The review synthesizes evidence on mosquito ecological dynamics within these habitats, including life stage distribution, habitat preferences, and the role of microenvironmental factors such as temperature, water retention, and chemical leachates. It further highlights the potential public health implications, as these habitats amplify mosquito-human interactions and elevate the risk of vector-borne disease transmission, notably dengue, chikungunya, and West Nile virus. The review underscores the importance of integrated waste management, urban planning, and community engagement as critical strategies to mitigate mosquito proliferation linked to plastic waste. Finally, it identifies key research gaps, particularly the need for longitudinal studies on PWH dynamics and their interactions with mosquito populations under varying climatic and Urbanization gradients. Addressing these emerging challenges requires a multidisciplinary approach that bridges entomology, public health, waste management, and urban ecology